Beneficial Effects of AMPK Agonists in Kidney Ischemia Reperfusion: Autophagy and Cellular Stress Markers - Declèves, Anne-Emilie (Nephron Exp Nephrol, 2014)
BACKGROUND: Kidney ischemia-reperfusion is a form of acute kidney injury resulting in a cascade of cellular events prompting rapid cellular damage and suppression of kidney function. A cellular response to ischemic stress is the activation of AMP-activated protein kinase (AMPK) where AMPK induces a number of homeostatic and renoprotective mechanisms, including autophagy. However whether autophagy is beneficial or detrimental in ischemia-reperfusion remains controversial. We investigated the effects of agonist induction of AMPK activity on autophagy and cell stress proteins in the model of kidney ischemia-reperfusion. METHODS: AMPK agonists, AICAR (0.1g/kg) and Metformin (0.3g/kg), were administered 24 hours prior to ischemia, with kidneys harvested at 24 hours of reperfusion. RESULTS: We observed a paradoxical decrease in AMPK activity accompanied by increases in mTORC1 activity and p62/SQSTM1 expression. These results lead us to propose that AMPK and autophagy was insufficient to properly counter the cellular insults in ischemia-reperfusion. Agonist induction of AMPK activity with AICAR or metformin increased macroautophagy protein LC3 and normalizes p62/SQSTM1 expression and mTOR activity. Ischemia-reperfusion increases in Beclin-1 and PINK1 expressions, consistent with increased mitophagy, were also mitigated with AMPK agonists. Stress responsive and apoptotic marker expressions increase in ischemia-reperfusion and are significantly attenuated with agonist administration, as are early indicators of fibrosis. CONCLUSIONS: Our data suggest that levels of renoprotective AMPK activity and canonical autophagy are insufficient to maintain cellular homeostasis contributing to the progression of ischemia-reperfusion injury. We further demonstrate that induction of AMPK activity can provide beneficial cellular effects in containing injury in ischemia-reperfusion.